Why teachers stay: the influence of faculty transformational leadership on job embeddedness - Chen Xin; Azlin Norhaini Mansor; Salleh Amat (Intelektual Pustaka Media Utama, 2026)
This study examined the relationship between transformational leadership and job embeddedness among faculty members in private universities in Sichuan Province, China. Using a stratified random sampling method, data were collected from 368 respondents through a structured questionnaire. Descriptive statistics revealed that both transformational leadership and job embeddedness were perceived at relatively low levels, with only certain dimensions such as individualized consideration and sacrifice rated at moderate levels. Correlation analyses indicated significant positive associations between transformational leadership and job embeddedness. Simple regression results demonstrated that transformational leadership significantly predicted job embeddedness, while multiple regression analysis showed that inspirational motivation and individualized consideration were the most influential dimensions. Moreover, SPSS process moderation analyses revealed that no key demographic variable significantly moderated the relationship between transformational leadership and job embeddedness. This study contributes to the literature by providing empirical evidence from China’s private higher education sector and offers practical implications for strengthening leadership practices and organizational strategies aimed at enhancing faculty retention.